Voices of the Poor : Crying Out for Change - Narayan, Deepa; Chambers, Robert; Shah, Meera K.; Petesch, Patti (New York: Oxford University Press for the World Bank, 2013)
As the second book in a three-part series entitled Voices of the Poor, "Crying out for Change" accounts for the voices from comparative fieldwork among twenty three countries. Through participatory, and qualitative research methods, the book presents very directly, poor people's own voices, and the realities of their lives. It outlines the multidimensional aspects of well-being, and how poor people see it, highlighting that in material terms, "enough" is not a lot for a good life, and, analyzes social well-being, security, and freedom of choice and action, in contrast to the "ill-being" aspects of material absence, reflecting on the experiences of humiliation, shame, anguish. and grief. The struggle for livelihoods is described through the scarcity of rural production, the diversified cities' bondage, and, the limited opportunities of life, and individual breakthroughs challenging their livelihoods. Further analysis reflect on the inadequacy, isolation, and lack of access to infrastructure; on the health aspects of mind and body; on gender relations in troubled subjugation; on social exclusion; and, on the uncertainties for survival. It finally challenges the meaning of development, and of power, calling for change, from material poverty to adequate assets and livelihoods, from exclusion to inclusion, organization, and empowerment.